Altered purine metabolism at reperfusion affects clinical outcome in lung transplantation. Issue 3 (21st April 2022) - Baciu, Cristina; Shin, Jason; Hsin, Michael; Cypel, Marcelo; Keshavjee, Shaf; Liu, Mingyao
Abstract : Introduction: Lung transplantation is an established treatment for patients with end-stage lung disease. However, ischaemia reperfusion injury remains a barrier to achieving better survival outcomes. Here, we aim to investigate the metabolomic and transcriptomic profiles in human lungs before and after reperfusion, to identify mechanisms relevant to clinical outcome. Methods: We analysed 67 paired human lung tissue samples collected from 2008 to 2011, at the end of cold preservation and 2 hours after reperfusion. Gene expression analysis was performed with R. Pathway analysis was conducted with Ingenuity Pathway Analysis. MetaboAnalyst and OmicsNet were used for metabolomics analysis and omics data integration, respectively. Association of identified metabolites with transplant outcome was investigated with Kaplan-Meier estimate and Cox proportional hazard models. Results: Activation of energy metabolism and reduced antioxidative biochemicals were found by metabolomics. Upregulation of genes related to cytokines and inflammatory mediators, together with major signalling pathways were revealed by transcriptomics. Purine metabolism was identified as the most significantly enriched pathway at reperfusion, based on integrative analysis of the two omics data sets. Elevated expression of purine nucleoside phosphorylase ( PNP ) could be attributed to activation of multiple transcriptional pathways. PNP catabolised reactions were evidenced by changes in related metabolites, especially decreased levels of inosine and increased levels of uric acid. Multivariable analyses showed significant association of inosine and uric acid levels with intensive care unit length of stay and ventilation time. Conclusion: Oxidative stress, especially through purine metabolism pathway, is a major metabolic event during reperfusion and may contribute to the ischaemia reperfusion injury of lung grafts.